2020
DOI: 10.1002/jcp.29733
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR‐181a‐5p inhibits retinal neovascularization through endocan and the ERK1/2 signaling pathway

Abstract: Retinal neovascularization (RNV) is a common pathological feature of angiogenesis‐related retinopathy. Endocan inhibition has previously been reported to suppress RNV in oxygen‐induced retinopathy (OIR); however, its molecular mechanisms remain to be elucidated. Here, we investigated the role and mechanism of endocan in OIR. We established an OIR mouse model and detected aberrant endocan overexpression in OIR mouse retinas. Endocan inhibition through small interfering RNA or a neutralizing antibody inhibited v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…The main positive finding of this study is that levels at baseline of miR-181a are negatively associated with baseline CAT, suggesting that miR-181a levels decrease when CAT increases. This finding seems in line with a recent study which reported that miR-181a is enriched in the normal mouse retina, but reduced in the retinas of mice in an oxygeninduced retinopathy (OIR) model [15]. The downregulation of miR-181a was accompanied by the upregulation of its target gene endothelial cell-specific molecule 1 (endocan or ESM-1), which has previously been identified to be highly enriched in retinal endothelial tip cells [23], and which has been shown to play an important role in the regulation of angiogenesis [24].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The main positive finding of this study is that levels at baseline of miR-181a are negatively associated with baseline CAT, suggesting that miR-181a levels decrease when CAT increases. This finding seems in line with a recent study which reported that miR-181a is enriched in the normal mouse retina, but reduced in the retinas of mice in an oxygeninduced retinopathy (OIR) model [15]. The downregulation of miR-181a was accompanied by the upregulation of its target gene endothelial cell-specific molecule 1 (endocan or ESM-1), which has previously been identified to be highly enriched in retinal endothelial tip cells [23], and which has been shown to play an important role in the regulation of angiogenesis [24].…”
Section: Discussionsupporting
confidence: 92%
“…The downregulation of miR-181a was accompanied by the upregulation of its target gene endothelial cell-specific molecule 1 (endocan or ESM-1), which has previously been identified to be highly enriched in retinal endothelial tip cells [23], and which has been shown to play an important role in the regulation of angiogenesis [24]. The intraocular injection of miR-181a resulted in the suppression of retinal neovascularization in the OIR model [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retinas were collected for RNA extraction. RNA isolation was performed as described previously [ 15 ]. In brief, total RNA was extracted from OIR and normal retina samples using TRIzol reagent (Thermo Fisher Scientific, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…They are key regulators of vessel development [ 13 ] and contribute to the formation of pathological RNV [ 9 , 14 ]. Recent studies have extensively characterized the involvement of miRNA-mediated regulation in retinal angiogenesis [ 15 ], proliferation [ 16 ], apoptosis, and migration. Alterations in miRNA expression have been studied in different signaling pathways involved in the progression and pathogenesis of RNV.…”
Section: Introductionmentioning
confidence: 99%